Haematological Profile After Use of Titanium Double Shanked Ligation Clips in Laparoscopic Appendectomy: An Experimental Study on Rat Model - Amela BAJRIĆ (University of Kafkas, 2021)
The aim of the study was to determine possible adverse effects on haematological parameters of the rats, using different surgical techniques, i.e. titanium double shanked ligation (DS) clips and endoloop polyglactin 910 suture material in laparoscopic appendectomy. The use of DS clips and other similar methods is not widely represented in veterinary surgery, as is the case in humans. Fifty rats were randomized into three groups: group 1 in which the appendiceal base was closed with a endoloop polyglactin 910 ligatures, 20 rats, group 2 in which the appendectomy was closed with DS titanium clips, 20 rats. Group 3 was the control, in which the animals were not subjected to the surgical procedure, 10 rats. Blood was drawn from the caudal vein of ten animals from each experimental group, 7 and 28 days post-surgery. Thrombocytopenia was found in the DS clips group, and hypochromia with hypochromic erythrocytes, as well as neutrophilia and lymphopenia in both experimental groups. From a haematological standpoint, DS clips are more applicable for potential patients than endoloop polyglactin 910 ligatures.